2016
DOI: 10.1016/j.clinph.2016.06.023
|View full text |Cite|
|
Sign up to set email alerts
|

Graph analysis of EEG resting state functional networks in dyslexic readers

Abstract: Graph metrics relate to the intrinsic organization of functional brain networks. These metrics provide additional insights on the cognitive deficits underlying dyslexia and, thus, may advance our knowledge on reading development. Our findings add to the growing body literature suggesting compromised networks rather than specific dysfunctional brain regions in dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
124
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 60 publications
14
124
1
2
Order By: Relevance
“…The goal of the present study was to examine the organization of functional networks in dyslexics and typically reading adults, extending our previous findings in 3rd grade children (Fraga González et al, 2016). We used PLI to assess connectivity and MSTs to examine the topological properties of the network.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The goal of the present study was to examine the organization of functional networks in dyslexics and typically reading adults, extending our previous findings in 3rd grade children (Fraga González et al, 2016). We used PLI to assess connectivity and MSTs to examine the topological properties of the network.…”
Section: Discussionsupporting
confidence: 54%
“…Our previous study reporting the results of MST analysis in dyslexic and typically reading children, we observed a somewhat different pattern of results (Fraga González et al, 2016). In that study, dyslexic children showed a less integrated tree configuration in theta, indicated by lower leaf number, degree and kappa, compared to typical readers.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations